Reviewing the current treatment approaches for vitiligo - analysis of literature - Daniel Ślusarczyk; Bartłomiej Żmuda; Wiktoria Jakubowska; Piotr Pisera; Aleksandra Kiełkowicz; Zuzanna Popińska; Filip Pactwa; Michał Żuberek (Kazimierz Wielki University, 2023)
Introduction: Vitiligo is a relatively common systemic, idiopathic disease within the spectrum of pigmentary disorders. Clinically, it presents as depigmented patches on the skin, resulting from the loss or dysfunction of melanocytes. Despite not impacting life expectancy, vitiligo should not be perceived merely as a cosmetic defect, given its potential to burden daily life and the frequent experiences of stigmatization by patients. Aim of the study: The aim of this study was to summarize the existing knowledge regarding the treatment of vitiligo. The current treatments in practice, alongside potential new methods, were summarized and described. Materials and methods: The literature available in the PubMed database was reviewed using the following keywords: "Vitiligo", "Vitiligo treatment", "Vitiligo new treatment methods", "Targeted therapies for vitiligo". Conclusions: Vitiligo is a multifactorial and still inadequately understood disorder, leading to a lack of fully safe and effective treatment. As in the management of other diseases, there should be a push for highly personalized treatments for patients. This approach takes into account the differences among patients and ensures a better chance of a positive clinical response. To achieve this goal, it's necessary to explore new treatment methods and expand ongoing research efforts. Also, raising awareness of vitiligo is key to increasing acceptance, support and understanding for those affected by the disease.